THE DEVELOPMENT OF A SCALE FOR PREDICTING MOTHERS COMPLIANCE IN THE EXPANDED PROGRAMME ON IMMUNIZATION (EPI) (1989)
The apparent high drop out rate in Expanded Programme on Immunization (EPI) is constituting a major barrier in the break-through of the child survival programme especially in developing countries of the World (Alakija, 1986). This cross-sectional, descriptive and explorative study was carried out in Obokun Local Government Area (LGA), Oyo State of Nigeria between October, 1987 and July, 1988. The study population consists of mothers who attended EPI clinics for their children’s immunization under the Expanded Programme on Immunization. Respondents were mothers whose children bad taken the first doses of diphtheria, pertussis, tetanus and Oral polio vaccines (DPT/OPV) between October 1987, and January, 1988. These mothers were classified as compliers if by the end of July, 1988 they had completed the three doses of DPT/OPV schedules. Those who had not completed these three doses were termed non-compliers. Out of 121 mothers used in the study, 65 were compilers while 56 were non-compliers. Data gathering tools used included questionnaire to explore demographic, attitudinal and cognitive factors in these mothers which may affect compliance with EPI appointment schedules. In addition, observational check-list was used to probe into factors which may affect compliance due to clinic settings or arrangements. After analysis of the data, the identified compliance factors were scored to form a predicting scale that can be used to identify those that are likely not to comply with appointment schedules among mothers in EPI Programme so that measures that will make them comply can be instituted from the start. The result showed that the respondents in both compilers and non-compilers were similar in such demographic characteristics as age, marital status and parity. They however differ significantly in demographic characteristics such as educational levels, occupation, income and religion. Also, there were more compilers among mothers who attended orthodox form of ante-natal services, those who had institutionalized deliveries and mothers who brought their children to have first contacts of immunization within their six months of lives. The risk factors that can determine non-compliance with appointments in EPI based on the findings of the study are low- educational level, low income, semi-skilled and non-occupation, non attendance of Orthodox ante-natal services in pregnancy, no immunization during pregnancy, non-institutionalized deliveries, long distance from home to EPI centres, giving herbs as protection to children, delaying the first immunization till children reached ages six months and lastly religions of mothers in which case muslims can default more than Christians. Based on the findings from the study, it is recommended that the health education approach in EPI be modified to include local communication system for rural women since effective communication is the key to implementation of health education activities. In addition future studies should focus on production of predictor scale that will enable the identification of non- compliance among urban/cities mothers.